Peran Forum Kerukunan Beragama (FKUB) Dalam Memperkuat Dakwah Moderasi Beragama Di Era Digital: Tinjauan Literatur - Umar Yadi Idris; Faizah (UIN Mataram, 2025)
Digital transformation has changed the pattern of da'wah and religious practices in Indonesia, while giving birth to new problems such as disinformation, intolerance, and religious polarization. In this situation, the Forum for Religious Harmony (FKUB) has a strategic position to mainstream da'wah from a moderation perspective. However, FKUB's contribution in the digital space still lacks scientific attention, so studies are needed that can map the direction, form, and strategy of moderate da'wah that are relevant to be developed. This study uses a qualitative approach through literature studies with the literature review method. The study process is carried out through identification, selection, thematic classification, analysis-synthesis, and formulation of conceptual models. Literature sources include scientific articles, books, policies, and regulations related to FKUB and religious moderation, especially for the 2023–2025 period. The results of the study show that FKUB acts as a cross-faith mediator, social dialogue facilitator, and moderate da'wah agent who promotes the values of wasathiyah, tolerance, non-violence, and respect for local culture. In the digital realm, this role develops through the use of online platforms that open up opportunities for interfaith collaboration and moderation campaigns, but also presents challenges in the form of low digital literacy and extreme narrative competition. This study offers a conceptual model of moderate da'wah based on FKUB that emphasizes the value of moderation, participatory communication strategies, and optimization of digital technology. These findings provide a theoretical contribution to the development of moderate da'wah studies as well as practical recommendations for policies to strengthen religious moderation in Indonesia.